2018
DOI: 10.1007/s00261-018-1464-9
|View full text |Cite
|
Sign up to set email alerts
|

Combination transarterial chemoembolization and microwave ablation improves local tumor control for 3- to 5-cm hepatocellular carcinoma when compared with transarterial chemoembolization alone

Abstract: Combination therapy with TACE and microwave ablation improves local control and increases time to LTP for 3-5 cm HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
22
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
7
22
0
2
Order By: Relevance
“…Consistent with previously studies, our analysis demonstrates that an add‐on resection or ablation after initial TACE significantly extended the survival time and increased the percentage of patients who reached a 3‐year survival time . This suggests that add‐on resection/ablation works synergistically with TACE.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previously studies, our analysis demonstrates that an add‐on resection or ablation after initial TACE significantly extended the survival time and increased the percentage of patients who reached a 3‐year survival time . This suggests that add‐on resection/ablation works synergistically with TACE.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the add-on resection or ablation removes or necrotizes hypovascular HCC lesions that are refractory to cytotoxicity by TACE delivered chemicals. 57,58 In further analysis, vascular invasion was the only risk factor that compromised the long-term survival in patients who received the add-on resection and/or ablation after TACE. This finding reveals that the efficacy of the add-on resection and/ or ablation is effective in eliminating almost all of the factors that are required to achieve the 3-year survival in the group without resection and/or ablation after TACE.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous studies reported that TACE combined with MWA (TACE-MWA) was associated with several advantages in patients with unresectable HCC. [44][45][46] Firstly, liver dysfunction was a risk prognostic factor of long-term survival in HCC patients. It was previously shown that sustained TACE treatment was more likely to cause liver failure than the other local treatments or systemic treatments.…”
Section: Discussionmentioning
confidence: 99%